The Turkish Short Version of the Speech, Spatial, and Qualities of Hearing Scale (SSQ) for Clinical Use: Determining Reliability and Validity for People with and without Hearing Loss on the Basis of SSQ12-A, SSQ12-B, SSQ12-C - Çildir, Bünyamin; Kılıç, Samet; Özkişi, Başak; Tokgöz-Yılmaz, Suna (ENT Updates, 2021)
Objective: This study was aimed at analyzing the validity and reliability of a Turkish shortened version of Speech, Spatial and Qualities of Hearing (SSQ) scale for adults using hearing aids and/or cochlear implants. The analysis was based on three forms of the SSQ, namely, SSQ12-A, SSQ12-B, and SSQ12-C. Methods: A total of two hundred and fifty-eight individuals with moderate or moderate- to-severe (n = 98), severe or very severe hearing loss (n = 71) and normal hearing (n = 89) from four centers participated in our study. SSQ12-A was administered to individuals who were suffering from hearing loss, and with normal hearing but were not previously fitted with a hearing aid. SSQ12-B was distributed to individuals who had been using a hearing aid for at least 6 months, and SSQ12-C was administered to individuals who had been using cochlear implants for at least 6 months. SSQ12-A was then re-administered to 27 individuals with hearing loss for the reliability of the questionnaire. Results: The internal consistency and reliability of all the three questionnaires were high (Cronbach’s α = 0.96, α = 0.96, and α = 0.84, respectively). Individuals with moderate hearing loss derived higher scores than did the individuals with severe or very severe hearing in SSQ12-A and SSQ12-B. No statistically significant difference was found between the scores (p > 0.05) of the respondents in the first and second rounds of SSQ12-A administration. Conclusions: The Turkish shortened version of the SSQ is a valid and reliable questionnaire for assessing hearing function. The three forms of the SSQ12 are useful for evaluatinghearing impairment and in organizing rehabilitation programs.